2012
DOI: 10.1186/1472-6750-12-91
|View full text |Cite
|
Sign up to set email alerts
|

Generation and functional characterization of the anti-transferrin receptor single-chain antibody-GAL4 (TfRscFv-GAL4) fusion protein

Abstract: BackgroundThe development of vectors for cell-specific gene delivery is a major goal of gene therapeutic strategies. Transferrin receptor (TfR) is an endocytic receptor and identified as tumor relative specific due to its overexpression on most tumor cells or tissues, and TfR binds and intakes of transferrin-iron complex. We have previously generated an anti-TfR single-chain variable fragments of immunoglobulin (scFv) which were cloned from hybridoma cell line producing antibody against TfR linked with a 20 aa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Our previous studies also demonstrated that TfR Abs could recognize tumor cells with high efficiency in vitro and 131 I-TfR Ab displayed a feature of specific accumulation at tumor tissue in vivo (2325). Also these TfR Ab-modified therapeutic agents exhibit tumor-specific cytotoxic activities (2629).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies also demonstrated that TfR Abs could recognize tumor cells with high efficiency in vitro and 131 I-TfR Ab displayed a feature of specific accumulation at tumor tissue in vivo (2325). Also these TfR Ab-modified therapeutic agents exhibit tumor-specific cytotoxic activities (2629).…”
Section: Introductionmentioning
confidence: 99%
“…Targeted fused polypeptides are an emerging hotspot in targeted therapy for breast cancer. 23 , 24 There are a number of studies on the anticancer effect of targeted fused polypeptides in the treatment of breast cancer, including targeting the con-served transmembrane domain of human epidermal growth factor receptors, 25 29 glucose-regulated protein 78, 30 transferrin receptor, 31 and p53. 32 These targeted fused polypeptides exhibited a potent cell death inducing effect on tumor cells and a considerable suppressing effect on tumor growth and metastasis, indicating that the targeted fused polypeptide represents a promising targeted therapy strategy.…”
Section: Discussionmentioning
confidence: 99%
“…He and coworkers recognized a TfR mAb (monoclonal antibody) tailored nanomedicines for improved tumor targeting. They demonstrated that drug entrapped HPPS based nanomedicines adapted with explicit ligands could muddle to receptors on the surface of tumor cells, resulting in the accretion of nanomedicines on the exterior surface of targeted cells [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90]. It was concluded that developed HPPS based nanomedicine holds the potential to strengthen targeting to tumor cells and attains favored recognition by specific antibodies in a complex biological setting [91].…”
Section: Endogenous High-density Lipoprotein Derived Nanoparticlesmentioning
confidence: 99%